Theoretical proposal: integrating literary text within the teaching/learning of Italian as a foreign language in Cameroon - Mathias, Bikitik Hyppolite (Formazione & insegnamento, 2015)
The teaching/learning of Italian as a foreign language makes students express properly what they observe or perceive. It aims at actively developing the meaning of language and style, not at the passive acceptance of mere knowledge. Introducing students to scientific practice belongs to one of the objectives of the secondary school in Cameroonian educational system. Where should Italian texts be placed in such a context? Which are the best texts to choose? The explanation of these two aspects will be dedicated to the study of the existing link between text and Italian language, language, culture and literature. In the end, we will try to answer the following question: “Which is the best literary text for the teaching of Italian in Cameroon?”.